Literasi Keuangan dan Pencatatan Keuangan Pribadi Sederhana bagi Siswa/I SMA - Amin Wijoyo; Steven Wiryajaya; Richard Edbert (Lembaga Pengembangan Kinerja Dosen, 2026)
Financial literacy is an essential competency that should be developed from an early age to enable students to manage their personal finances wisely amid the growing use of digital financial transactions. However, many high school students are still unfamiliar with budgeting and systematic personal financial recordkeeping. This Community Service Program (PKM) aimed to improve students' understanding of financial literacy and simple personal financial recordkeeping through basic accounting training. The activity was conducted face-to-face at SMA Katolik Ricci 1 Jakarta involving 15 students using interactive lectures, discussions, case studies, practical exercises on personal financial recording, and learning evaluations through Kahoot-based pre-tests and post-tests. The results demonstrated an improvement in students' understanding of the learning materials. Based on the post-test results, 3 students (20%) achieved 100% accuracy, 6 students (40%) scored 83%, 3 students (20%) obtained 67%, and 3 students (20%) achieved 50% correct answers. Overall, 80% of participants attained at least 67% accuracy, indicating that most students successfully understood the concepts of financial literacy, personal budgeting, and simple income and expenditure recording. In addition, students actively participated in discussions and evaluation sessions, creating a more engaging learning environment. Therefore, this training effectively enhanced students' financial literacy and basic accounting knowledge while fostering responsible financial management behavior, contributing to the achievement of the Sustainable Development Goals.